(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
his study aims to evaluate the performance of master’s educated teachers at SMPN 31 Semarang, reviewed from their pedagogic and professional competence. The research method used is a qualitative approach, with data collected through observation and in-depth interviews. The data analysis process includes reading interview transcripts repeatedly and interpreting the meaning of the themes. The results of the study show that teachers with master’s education at SMPN 31 Semarang have good pedagogic competence, especially in systematic learning planning, the use of varied learning strategies (scientific and differentiated), and conducive classroom management. In professional competence, these teachers show a deep mastery of the material, are active in self-development through training and workshops, and have a high professional attitude. However, there are still obstacles such as administrative burden, limited time for self-development, and digital literacy for some teachers. The principal provides feedback and guidance through a forum for evaluating the performance of teachers and the learning community to overcome these obstacles.